2017
DOI: 10.3389/fphar.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate Affects Glial Function Increasing Oxidative Stress and Neuroinflammation in Chronic Kidney Disease: Interaction between Astrocytes and Microglia

Abstract: Indoxyl sulfate (IS) is a protein-bound uremic toxin resulting from the metabolism of dietary tryptophan which accumulates in patients with impaired renal function, such as chronic kidney disease (CKD). IS is a well-known nephrovascular toxin but little is known about its effects on central nervous system (CNS) cells. Considering the growing interest in the field of CNS comorbidities in CKD, we studied the effect of IS on CNS cells. IS (15–60 μM) treatment in C6 astrocyte cells increased reactive oxygen specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 70 publications
7
122
0
2
Order By: Relevance
“…In this study, we found that IS stimulation increased the phosphorylation of NF‐κB p65. This is consistent with the previous studies reported that IS has an effect on the activation of NF‐κB in vitro (Adesso et al, ; Shen et al, ). We further confirmed that inhibition of NF‐κB with its specific inhibitor Bay‐11‐7082 relieved IS‐induced osteogenic differentiations of HASMCs, which were characterized by an upregulation of osteogenic cell marker Cbfα1 and downregulation of α‐SMA, a specific smooth muscular cell marker.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found that IS stimulation increased the phosphorylation of NF‐κB p65. This is consistent with the previous studies reported that IS has an effect on the activation of NF‐κB in vitro (Adesso et al, ; Shen et al, ). We further confirmed that inhibition of NF‐κB with its specific inhibitor Bay‐11‐7082 relieved IS‐induced osteogenic differentiations of HASMCs, which were characterized by an upregulation of osteogenic cell marker Cbfα1 and downregulation of α‐SMA, a specific smooth muscular cell marker.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have shown that activation of NF‐κB is expressed at a higher level in calcified vessels and inhibition of NF‐κB eliminates the Pi or TNF‐induced VSMC calcification in vitro (He et al, ; Zhang et al, ; Zhao et al, ; Zhao et al, ), suggesting that NF‐κB may also play a crucial role in the pathological of VC in CKD patients. Recently, numerous studies have reported that IS stimulated the activation of NF‐κB in various cells involved in the vessel senescence, endothelium dysfunction, and neuroinflammation (Adelibieke, Shimizu, Muteliefu, Bolati, & Niwa, ; Adesso et al, ; Shen et al, ). Based on these findings, there may be a potential link between NF‐κB and IS in the pathogenesis of VC.…”
Section: Introductionmentioning
confidence: 99%
“…After 1 hour, the secondary antibody, in fixing solution, was added to the cells and cell fluorescence was evaluated by a fluorescence-activated cell sorter (FACSscan; Becton Dickinson) and analyzed by Cell Quest software (version 4; Becton Dickinson), as formerly reported. 22 2.1.8 | Immunofluorescence analysis for NF-κB and the nuclear factor erythroidderived 2 (Nrf2) by confocal microscopy IEC-6 cells were plated on coverslips in a 12-well plate (2 × 10 5 cells/well) and allowed to adhere for 24 hours. After the adhesion, the cellular medium was substituted with fresh medium with or without plumericin (1 µM) and incubated for 1 hour.…”
Section: Measurement Of Cyclooxygenase-2 (Cox-2) Inducible Nitricmentioning
confidence: 99%
“…High levels of metabolic end-products-the uremic toxins-have become clinically relevant in CKD progression and are tightly related to many CKD-associated complications [5][6][7][8][9][10][11]. CKD patients tend to suffer from many complications, such as hypertension, cardiovascular diseases, anemia, metabolic acidosis [12], altered immune response, mineral and bone disturbances and neurological complications [13]. Among these complications, cardiovascular dysfunctions and infections promoted by an altered immune response have been shown to be responsible for an increased risk of morbidity and mortality [14].…”
Section: Introductionmentioning
confidence: 99%